### Law of subtraction of logarithms:

`log_m(a)-log_m(b)=log_m(a/b)`

"When two logarithms (of the same base) are subtracted, the result is a logarithm of the quotient of the two logarithms"

The above law applies to logarithms with same bases, not with different bases.Note:

### Examples:

- `log_10(40)-log_10(2)=log_10(50/2)=log_10(25)`
- `log_m(x)-log_m(y)=log_m(x/y)`
- `log(x^2y^2)-log(xy)=log((x^2y^2)/(xy))=log(xy)`
- `log(6x)-log(9x)=log((6x)/(9x))=log(1/3)`

### Subtracting logarithms with different bases:

Logarithms with different bases can not be subtracted by the above mentioned law. However, by converting their bases to a common base, the logarithms can then be simplified as shown in the following example:
`log_2(20)-log_3(30)=(log(2))/(log(20))-log(3)/log(30)`

`= {log2 * log(30) - log(3) * log(20)}/{log(20) * log(30)}`

Hi to every single one, it's genuinely a nice for me

ReplyDeleteto visit this web page, it includes important Information.